PEMBELAJARAN YANG MENYENANGKAN: IMPLEMENTASI KURIKULUM MERDEKA - Alfaiz, Alfaiz; Andre, Julius; Fahriza, Irfan; Rachmaniar, Ananda; Dartina, Vina; Kadafi, Asroful (UNIVERSITAS PGRI MADIUN, 2023)
Abstract. This article aims to provide insight and knowledge to the academic community that a lesson has three aspects that need to be present in learning Logos, Ethos and Pathos, as well as the curriculum context that needs to be present in learning. In the setting of national seminar activities for the academic community, both education practitioners and students. The activity focuses on implementing BK in the independent campus curriculum. This service is carried out using the lecturing socialization method. As a result of this service, participants from this activity gain knowledge and understanding regarding what Logos, Ethos and Pathos are like and understand the implementation of the independent curriculum in a fun learning strategy setting, active participants in discussions and evaluating the results of the conference activities. Abstrak. Artikel ini bertujuan untuk memberikan wawasan dan pengetahuan pada masyarakat akademik bahwa suatu pembelajaran memiliki tiga aspek yang perlu ada dalam pembelajaran Logos, Etos dan Patos serta konteks kurikulum yang perlu ada dalam pembelajaran. Dalam seting kegiatan seminar nasional pada civitas akademika baik praktisi pendidikan, dan mahasiswa. Bahwasanya kegiatan focus pada menyampaikan bagaimana implementasi BK dalam kurikulum kampus merdeka. Pengabdian ini dilaksanakan dengan menggunakan metode lecturing socialization. Hasil dari pengabdian ini peserta dari kegiatan pengabdian ini mendapatkan pengetahuan dan pemahaman terkait seperti apa Logos, Etos dan Patos serta memahami pelaksanaan dari kurikulum merdeka dalam seting strategi pembelajaran yang menyenangkan, peserta aktif dalam diskusi dan mengevaluasi hasil dari kegiatan seminar.